Information modeling for lean manufacturing in supply chain management - Misam Kashefi Bagherian, 1981-; Mat Rebi Abdul Rani; Fakulti Kejuruteraan Mekanikal (2011)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2011